Role of Basin Width Variation in Tectonic Inversion: Insight from Analogue Modelling and Implications for the Tectonic Inversion of the Abanico Basin, 32°-34°S, Central Andes - Jara-Munoz, P (Geological Society of London, 2015)
We use analogue modelling to investigate the response of compressional deformation superimposed on an extensional basin with along-strike changes in width. Parameters described include extension and shortening distribution and directions, orientation of structures and degree of basin inversion. Two types of model are presented: in the first (Type I), an extensional basin is constructed with variable width (applying differential extension) and subsequently inverted by homogeneous shortening; in the second (Type II), an extensional basin with constant width is subsequently inverted by inhomogeneous shortening (differential compression). From our observations, we compare both types of model to structural patterns observed in some natural cases from the Central Andes. Both models generate oblique structures, but in the Type II model a significant rotation is characteristic. Our results suggest that in the Central Andes region between 32° and 33°S, the Abanico Basin may correspond to a basin of smaller area compared to the larger basin south of 33°S. Our Type I model further explains some patterns observed there, from which we conclude that the control exercised by the width of a pre-existing basin should be considered when interpreting the geological evolution of that area of the Andes. © 2015 The Geological Society of London.